10.1152/physiolgenomics.00169.2022 (CrossRef Listing of Deleted DOIs, 2000)
Age- and disease-related declines in brain health contribute to impairments in physical function, yet effective approaches to lessen these declines remain limited. Overall health is governed by a network of interdependent organ systems, such that dysfunction in one system can propagate across others. Although the brain has been viewed as a top-down regulator of vital functions, evidence indicates that cognition is affected by signals from peripheral organs. This interorgan communication likely explains the coexistence of Alzheimer's disease and related dementias with cardiovascular and metabolic disorders characterized by overlapping pathophysiology. Skeletal muscle and the peripheral vasculature are key contributors to this and represent modifiable systems that can alter brain structure and function. Skeletal muscle regulates myokine release through motor neuron function, contractile activity, and metabolic perturbations, thereby influencing neuroplasticity, mitochondrial function, and inflammatory signaling, and may affect measures of peripheral vascular function, like reactive hyperemia. Other properties of the vasculature, including arterial stiffness, directly affect cerebral perfusion and blood-brain barrier permeability. These systems form a muscle-vascular-brain axis that contributes to brain health and impacts the risk of cognitive impairment. Therefore, our aim was to synthesize the current understanding of interactions among skeletal muscle, the peripheral vasculature, and the brain, and their collective role in maintaining cognitive health. We also highlight recent clinical trials and emerging strategies affecting interorgan crosstalk. These conclusions support a model in which lifestyle interventions targeting peripheral systems, such as resistance training, may preserve brain health across all populations, offering scalable approaches applicable across the lifespan.